Way up north in Louisville : African American migration in the urban South, 1930-1970 - Adams, Luther (John Hope Franklin series in African American history and culture., 2010)
In the wake of World War II, when roughly half the black population left the South seeking greater opportunity and freedom in the North and West, the same desire often anchored African Americans to the South. Adams offers a powerful reinterpretation of the modern civil rights movement and of the transformations in black urban life within the contexts of migration, work, and urban renewal.